Targeting herpes simplex virus with CRISPR-Cas9 cures herpetic stromal keratitis in mice - Yin, Di (Nat Biotechnol, 2021)
Herpes simplex virus type 1 (HSV-1) is a leading cause of infectious blindness. Current treatments for HSV-1 do not eliminate the virus from the site of infection or latent reservoirs in the trigeminal ganglia. Here, we target HSV-1 genomes directly using mRNA-carrying lentiviral particles that simultaneously deliver SpCas9 mRNA and viral gene-targeting gRNAs (designated HSV-1-erasing lentiviral particles, HELP). We show that HELP efficiently blocks HSV-1 replication and the occurrence of herpetic stromal keratitis (HSK) in three different infection models. HELP was capable of eliminating the virus reservoir via retrograde transportation from corneas to trigeminal ganglia. Additionally, HELP inhibited viral replication in human-derived corneas without causing off-targeting effects as determined by whole genome sequencing. These results support the potential clinical utility of HELP for treating refractory HSK.